Bronsted acidic ionic liquid-catalyzed conversion of hemicellulose into sugars - Matsagar, Babasaheb M.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Development of a competent method for the conversion of hemicellulose, a lignocellulosic component, into sugars is essential. In a one-pot method, Bronsted acidic ionic liquid (BAIL)-catalyzed hydrolysis of hardwood hemicellulose at 160 degrees C in water media gave C5 sugars (xylose + arabinose) in 87% yield. The efficiency of the ILs and their acid strength both followed the similar trend, [C3SO3HMIM][HSO4] > [C3SO3HMIM][PTS] > [C3SO3HMIM][Cl] > [BMIM][Cl]. The ion-dipole-type interaction present between the BAIL and the substrate, which is proposed by the H-1 NMR study, is suggested to help in achieving better activity with BAIL than with mineral acid, H2SO4.

Conversion of concentrated sugar solutions into 5-hydroxymethyl furfural and furfural using Bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Munshi, Mudassir K.; Kelkar, Ashutosh A.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Catalytic amounts of recyclable Bronsted acidic ionic liquids (BAILs) yielded HMF (73%) and furfural (81%) with high selectivity from highly concentrated solutions of D-fructose (40 wt%) and D-xylose (3 wt%), respectively. With a 6 wt% D-xylose solution, 73% yield was observed. An activity-property correlation of BAIL is established.

Direct production of furfural in one-pot fashion from raw biomass using bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Hossain, Shahriar A.; Islam, Tofazzal; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. W. (Scientific Reports, 2017)
The conversion of raw biomass into C5-sugars and furfural was demonstrated with the one-pot method using Bronsted acidic ionic liquids (BAILs) without any mineral acids or metal halides. Various BAILs were synthesized and characterized using NMR, FT-IR, TGA, and CHNS microanalysis and were used as the catalyst for raw biomass conversion. The remarkably high yield (i.e. 88%) of C5 sugars from bagasse can be obtained using 1-methyl-3(3-sulfopropyl)-imidazolium hydrogen sulfate ([C3SO3HMIM][HSO4]) BAIL catalyst in a water medium. Similarly, the [C3SO3HMIM][HSO4] BAIL also converts the bagasse into furfural with very high yield (73%) in one-pot method using a water/toluene biphasic solvent system.

ffects of cations, anions and H+ concentration of acidic ionic liquids on the valorization of polysaccharides into furfural - Matsagar, Babasaheb M.; Dhepe, Paresh L. (New Journal of Chemistry, 2017)
The valorization of hemicellulose into valuable chemicals, such as C5 sugars and furfural, in a one-pot fashion is crucial. In this work, acidic ionic liquids in the presence of water showed high yields of C5 sugars (>80%) with >99% conversion of hemicelluloses at 160 degrees C. With a water + toluene biphasic solvent system, within 4 h, an 85% furfural yield was obtained directly from hemicellulose in a one-pot fashion using a catalytic amount of 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate. It was seen that Bronsted acidic ionic liquids (BAILs) perform better than solid acid [Faujasite and Mordenite zeolites; ion exchange resin, Amberlyst-15] and mineral catalysts [HCl and H2SO4]. The higher activity of BAILs compared to solid acids and mineral acids was correlated to the Hammett acidity function (Ho) and ion-dipole type of interactions. The catalysts were characterized using NMR (H-1 and C-13), elemental analysis and TGA to confirm that they were stable under reaction conditions and were thus recyclable.

Glucose isomerization catalyzed by bone char and the selective production of 5-hydroxymethylfurfural in aqueous media - Matsagar, Babasaheb M.; Van Nguyen, Chi; Hossain, Md. Shahriar A.; Islam, Md. Tofazzal; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. -W. (Sustainable Energy & Fuels, 2018)
The selective production of 5-hydroxymethylfurfural (HMF) is important, and it is difficult with glucose substrates in a water solvent. Here we demonstrate a selective method for glucose-to-HMF conversion using the combined catalysis of bone char and 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate acidic ionic liquid catalysts with a high HMF selectivity (54%) in water.

High surface area nanoporous carbon derived from high quality jute from Bangladesh - Khan, Junayet Hossain; Lin, Jianjian; Young, Christine; Matsagar, Babasaheb M.; Wu, Kevin C. W.; Dhepe, Paresh L.; Islam, Md Tofazzal; Rahman, Md Mahbubur; Shrestha, Lok Kumar; Alshehri, Saad M.; Ahamad, Tansir; Salunkhe, Rahul R.; et al. (Materials Chemistry and Physics, 2018)
We report an economically viable and environment-friendly strategy for the preparation of nanoporous carbon (NC) from jute which is one of the most abundant natural fibers produced in Bangladesh and some South Asian countries. Nitrogen adsorption-desorption isotherms, X-ray diffraction, Raman spectroscopy, UV spectroscopy, and scanning/transmission electron microscopy were performed to characterize the obtained NC. Three different types of jute-derived NCs have been synthesized at three different temperatures, 700 degrees C, 800 degrees C and 900 degrees C. The NC prepared at 800 degrees C resulted in a high surface area (981 m(2) g(-2)) and was associated with the retention of the original fibrous shapes. This study shows a promising future for jute as a natural precursor for NCs for a myriad of applications ranging from water purification to gas separation to energy conversion and storage.
Keywords: Adsorbents; Graphitization; Jute; Nanoporous carbons; porous materials

Lignocellulosic biomass analysis: acidic lignin recovery, characterisation, and depolymerisation - Singh, Sandip K.; Matsagar, Babasaheb M.; Dhepe, Paresh L. (Biomass Conversion and Biorefinery, 2024)
For the development of an effective lignocellulosic biomass conversion technology to biofuels and chemicals, the biomass composition analysis and their properties need to be characterised prior to biomass valorisation, including polysaccharide hydrolysis and lignin depolymerisation. In this work, a facile colorimetric titration method for the quantification of alpha-, beta-, and gamma-cellulose, pentosan, lignin, and silica percentages of wheat straw (WS) and two bagasse (BG I and II) samples was done. The result showed higher amounts of structural biopolymers (i.e. holocellulose and lignin (similar to 89.3%)) in BG compared to WS (81%) sample. Lignin recovery from BG (I and II) and WS samples was done by applying two-stage concentrated and dilute sulphuric acid hydrolysis, and maximum recovery (i.e. 21.5%; acid soluble +insoluble) of lignin obtained from BG II sample. Elemental and composition analysis results were represented substantial differences in lignin properties, including higher heat values (19.8 MJkg(-1)) of recovered lignin from BG II as well as high amounts of silica percentage from WS lignin. An intense Si-O-Si asymmetric stretching mode and/or C-O-C aliphatic aromatic ether (similar to 1100 cm(-1)) was characterised for lignin derived from WS. C-13 CP-MAS NMR exhibited variable intensities for dibenzodioxocin, spirodienone, and tricin moieties in recovered lignin samples. These lignin samples were processed for depolymerisation using homogeneous (1-methyl-3-(3-sulphopropyl)-imidazolium hydrogen sulphate) and heterogeneous (immobilised Bronsted acidic ionic liquid) catalysts to lower molar mass aromatic fractions and represented 89% and 92% organic solvent-soluble product yields respectively from WS-derived lignin.
Keywords: bagasse; Dibenzodioxocin; Holocellulose; Lignin depolymerisation; Spirodienone; Tricin; Wheat straw